Evaluating relationship implementations performance in object-relational databases - Golobisky, María Fernanda (2007)
In this work an evaluation of an object-relational schema implementation representing different relationships of an UML class diagram against the relational approach was made. To perform this test we have implemented both object-relational and relational schemas from a UML class diagram in a commercial database leader in the market. The main goal has been to prove the competitiveness of the object-relational technology. The methodology used for this work was to present several schema implementations of association, composition, aggregation and inheritance relationships, propose a set of representative queries to evaluate their behavior, compare the results and make an analysis based on response times. Four alternatives implementations of the schema diagram were made for a composition relationship presented in the proposed UML class diagram. The queries have been executed with no flush to the database buffer pool among runnings to simulate a real situation. In some object-relational queries several built-in functions and operations have been used. As a consequence of this work we are proposing some extensions to the relational schema diagram to add the object-relational alternatives (references, arrays, multisets, etc.) proposed by the SQL:2003 standard.